Effects of Capsaicin on Migration and Alkaline Phosphatase Activity of Dental Pulp Cells - Khonglim, Kittipot; Chuenjitkuntaworn, Boontharika; Tamura, Yukihiko; Fuangtharnthip, Pornpoj (European Journal of Dentistry, 2024)
Objectives Dental pulp, a specialized mesenchymal tissue within teeth, is pivotal in dental health and tissue repair. Capsaicin, the primary pungent component of chili peppers, is known for its diverse pharmacological properties. While capsaicin's effects on various cell types have been studied, its impact on dental pulp cells remains relatively unexplored. This study investigated the influence of pure capsaicin extract on dental pulp cell behavior, focusing on cell viability, proliferation, migration, and alkaline phosphatase (ALP) activity.Materials and Methods Capsaicin solution was prepared and diluted to various concentrations (1 nM, 0.01 µM, 0.1 µM, 1 µM, 10 µM, and 100 µM), then was tested on rat dental pulp cells (RPC-C2A). Cell viability and proliferation were assessed using the MTT assay. Boyden chamber tests and wound healing were used for evaluating cell migration. The activity of ALP was determined to show cell function during dental pulp repair.Statistical Analysis The data were analyzed using a one-way analysis of variance or an independent-sample Kruskal–Wallis, followed by multiple comparison tests.Results Capsaicin of 100 µM exhibited cytotoxicity, whereas those with lower concentrations stimulated cell proliferation. Wound healing assays revealed increased cell migration, particularly when cultured with 1 nM capsaicin (p = 0.002). Boyden chamber assays demonstrated enhanced cell invasion without statistical significance. ALP activity of dental pulp cells increased significantly at 1 nM (p < 0.001) and 1 µM (p = 0.021) capsaicin concentrations, indicating potential dentinogenesis and pulp repair.Conclusion Capsaicin of lower concentrations, less than 10 µM, is likely to promote proliferation, migration, and ALP activity of dental pulp cells. Our findings offer potential applications for capsaicin as a medication for dental pulp repair.
Keywords: capsaicin; dental pulp; cell migration; alkaline phosphatase activity